Biologics in General Medicine - Boehncke, W.-H; Radeke, H.H (Springer Berlin Heidelberg : Imprint: Springer, 2007)
The idea for this book was born during the symposium on biologics organized by ZAFES (Center for Drug Research, Development and Safety at the University of Frankfurt am Main) in September 2005. Highly distinguished researchers special- ing in the field of biologics had gathered together to exchange information on this relatively new subject. Realizing that this symposium was one of the few sources of condensed information on biologics, it became obvious that we had to create a means of informing an interested wider circle of scientists and especially general c- nicians. Therefore, the editors of this book suggested to the researchers at the symposium andalsotoprominent scientists andcliniciansinvolvedinthe developmentand application of biologics as their major field of interest the idea of assembling this compendium. We received an overwhelmingly positive response - thankfully also from the publisher - most being more than willing to support this innovative project with highly relevant chapters on the latest state of the art. As we were eager to fill the information gap with up-to-date knowledge, the project had to be finished within the shortest time possible. To all experienced with editing this was obviously a ch- lengeand we areverythankfultoall thecontributorsthatour timeline hadtobe extended by only a few months. This book represents a collection of the most recent knowledge on biologics written by people who have been active in the field for many years. Wolf-Henning Boehncke Heinfried H. Radeke Contents 1 Introduction: Definition and Classification of Biologics W. -H. Boehncke, H. H. Radeke . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .